(untitled) (Global Journal of Management and Business Research, 2013)
Fast and frequent change in technology has put the present day employee under pressure. This pressure has impact on employee’s personality dimensions and consequently on employee’s performance. So, one of the most critical issue of modern era is to study the impact of changing psychological dimensions on employee’s performance. This research was aimed to study effects of improved psychological traits like self image and agreeableness on employee performance. Statistical universe for this study was the employees having experience of more than three years from governmental and non-governmental organizations. Employee Performance, Agreeableness and self image among managers were assessed by using the employee performance inventory developed by researchers, Agreeableness Measuring Scale (AMS) (Rishipal & Jain, N., 2012) and The State Self-Esteem scale (SSES) (Heatherton & Policy, 1991) respectively. A crosssectional and longitudinal study was conducted by using the before and after with control group research design to compare the performance of treatment group consisting of the low performer employees having lower tendency of agreeableness and self-image and control group consisting of the high performer employees having higher tendency of agreeableness and self-image. Control and treatment group were formed by adopting the sampling technique of randomization on availability basis.